Students' Perception of Translanguaging Practices in The Department of English Education, Mulawarman University - Safira Amru Rijamil; Istanti Hermagustiana; Yuni Utami Asih; Susilo Susilo; Effendi Limbong (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study explores translanguaging practices in the Department of English Education at Mulawarman University, focusing on how lecturers implement these strategies and how students perceive their impact on learning. The background of this research arises from the challenges faced by students in English as a Foreign Language (EFL) contexts, where limited exposure to English often hampers comprehension and reduces classroom participation. The objective of the study is twofold: to identify the forms of translanguaging employed by lecturers and to examine students’ perceptions, engagement, and responses toward these practices. This research applied a qualitative case study design, collecting data through classroom observations and semi-structured interviews with selected students, followed by thematic analysis supported by triangulation of data sources and methods. The findings demonstrate that lecturers commonly applied code-switching, bilingual clarification, and double questioning techniques to simplify abstract concepts and encourage classroom interaction. Students reported that translanguaging significantly reduced language anxiety, boosted confidence, and facilitated more active participation. Moreover, it improved comprehension by allowing learners to connect complex academic content in English with their first language. These findings highlight translanguaging not merely as spontaneous language switching but as a deliberate pedagogical strategy that scaffolds learning, fosters inclusivity, and validates students’ multilingual identities. Nevertheless, challenges were also noted, such as the risk of overreliance on the first language, which may reduce immersion for advanced learners, and the necessity for structured implementation to maintain discourse coherence. In conclusion, translanguaging has proven to be an effective instructional approach in multilingual EFL classrooms. It supports deeper understanding, enhances student engagement, and nurtures identity affirmation. However, proportional and systematic application is essential to maximize its benefits while minimizing potential drawbacks.